PERAN PEMERINTAH KABUPATEN GROBOGAN DALAM PENGEMBANGAN PASAR AGRO HORTIKLUTURA - dyah ayu dewanti; turtiantoro .; nur hidayat sardini (Journal of Politic and Government Studies, 2016)
This recearch is based on the lack of marketing land for transaction activity of regional agriculture products which is causing people open their own trade space illegally existing in Grobogan Regency, exactly in Ahmad Yani St. This is causing aesthetic, sanitation, and city comfort distrurbance and also causing traffic jam around the location. This research will be describe the role of Grobogan Regency Government in overcoming that which based on Perbup No. 35 in 2008 contained Main Tasks, Function, Description of Position’s Tasks and Working Procedure of Department of Industry’s Organization, Trade, Mining and Energy Grobogan Regency. This research aims to identify the role of Grobogan Regency Government in the way to develop Agro Holticulture Market.Type of this research is qualitative by phenomenological approach. Source of data is found from primary data through interviewing the informant or key person by Purposive Sampling Technique. Meanwhile, the secondary data comes from document data, archives, and other sources relate to this research. Collecting data technique in this research uses interview, observation, and documentation. Meanwhile, analysis techique wich is used in this research is qualitative data analysis by analyzing in the form of explanation, description and concluding of indication which is researched.Result of this research is found that the role of Grobogan Regency Government in Developing Agro Holticulture Market is as a policy functionary, by the activities such as development, data colletion, collecting and booking tax and controlling admnistration management of regional market. Other result in field shows that Agro Holticulture Market’s development from year to year is increasing continually whether from total sellers side, incresing of rent result every year and increasing of Locally Generated Revenue through market retribution. This is of course not separated from local government’s role as an actor in the way to develop Agro Holticulture Market.Keywords: Role of Government, Agro Holticulture Market, Grobogan Regency.